Development of Guided Inquiry-based E-Worksheet to Stimulate Science Process Skills on Light Diffraction Materials - Handayani, Meita Puteri; Munna, Kamila; Herlina, Kartini; Suyatna, Agus; Viridi, Sparisoma (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Understanding light diffraction requires higher-order thinking and the ability to apply science process skills. Therefore, this study aims to develop a guided inquiry-based e-worksheet that is valid, practical, and effective to stimulate science process skills in Light Diffraction materials. The study uses the Design and Development Research (DDR) approach, which consists of four stages: analysis, design, development, and evaluation. The data analysis uses a validity test assessed by three experts, a practicality test conducted by students and teachers, and an effectiveness test as measured by the N-Gain test. The validity test results obtained an average value of 3.54, which is